The Role of Islamic Religious Education in Shaping the Character of Children in Banyuurip Village in the Digital Era - Dwi Indah Rachmawati; Dara Jihan Anjania; Maulana Aqil Lubis; Achmad Muchlis Ali; Cantika Khoiriyah Oktavianti; Yulia Rahma Wati; Lisda Sabrina; Ernik Noviyanti; Ana Zahrotun Nihayah (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to explore the role of Islamic Religious Education in shaping children's character in the digital era. The research involves a literature review to examine relevant studies and articles, and identify Implications for the educational world. The findings indicate that Islamic Religious Education plays a crucial role in character development for children in the digital age. In addition to teaching religious values, Islamic Religious Education also includes ethical and moral learning essential for children. The study reveals that Islamic Religious Education is effective in imparting moral values, developing digital ethics, and fostering spiritual awareness in technology use. The implications of this research include aspects of ethics and morals in technology use, the development of digital ethics, and the importance of parental involvement in shaping children's character in the digital era. This research is important for parents and teachers to understand in order to develop effective strategies for nurturing responsible, ethical, and integrity-driven character in children's digital lives. In this interconnected era, integrating Islamic moral and ethical values in education is cructal to ensure that children use technology wisely and responsibly.